New 2-indolinone-indole hybrid compounds carrying a benzoyl moiety as tyrosine kinase inhibitors - Camci-Eren, Merve; Cinek, Tugce; Cihan-Ustundag, Gokce; Ozen-Eroglu, Gunes; Yildirim, Merve; Genc-Akar, Oykum; Karali, Nilguen (Academic Press Inc Elsevier Science, 2025)
In this study, new 2-indolinone-indole hybrid compounds (4a-s) carrying a benzoyl moiety were synthesized and their cytotoxic effects were examined against pancreatic (MIA-PaCa-2) and colon (HT-29 and HCT-116) cancer cells by MTT assays. Most of the tested compounds exhibited a better inhibitory activity and safety profile than the reference standard sunitinib malate against MIA-PaCa-2 and HCT-116 cancer cells. Compound 4e displayed the greatest cytotoxic effect on HCT-116 cell with an IC50 value of 0.16 mu M and a remarkable selectivity profile (SI > 625). Compound 4g exhibited a selective activity against HCT-116 cancer cell (IC50 = 0.34 mu M), with no activity against the other cells at the highest concentrations tested. Compound 4b demonstrated a potent inhibitory activity against MIA-PaCa-2 cell (IC50 = 0.54 mu M). General tyrosine kinase inhibitor (TKI) activities and apoptotic effects were examined for compounds 4b, 4e and 4g. The tested compounds were observed to significantly reduce general TK activities in HCT-116 cell and induce apoptosis in HCT-116 and MIA-PaCa-2 cells. Lead compound 4e, the most effective general TKI, was determined to have a specific SRC kinase inhibitor effect in HCT-116 cell and the molecular modelling studies were performed to understand the potential binding mode at the ATP-binding domain of SRC kinase.
Keywords: 2-indolinone; Anticancer activity; Tyrosine kinase; SRC; Apoptosis